La radio en la prisión. Una estrategia de alfabetización mediática en beneficio del tratamiento penitenciario en España - Contreras-Pulido, Paloma; Thomas, Jérôme (Contratexto, 2024)
Prisoners in Spain also have the right to communicate and freely express their thoughts and ideas. This condition can be a reason to implement media literacy workshops in prisons, using radio as a tool for communication and expression. Even though they are not exempt from institutional control, as they are integrated into the so-called Individualized Penitentiary Treatment Plan, prisoners enhance their social and personal dimensions through these radio experiences, which function as a tool for rehabilitation and recovery. The article uses a qualitative methodology to analyze letters written by prisoners published in a book and interviews with 26 other inmates, all participants in Spanish prison radio programs, to understand their perception of the advantages of carrying out this activity. Through discourse analysis, it is possible to observe how they recognize improvements in their communication skills, self-perception of their abilities, enhanced self-esteem, improved relationships with others, and motivation to learn. The article concludes that these workshops help achieve the empowering objective of penitentiary treatment, although they still need a communication-oriented perspective.
Radio in prison. A media literacy strategy for the benefit of prison treatment in Spain
Rádio na prisão. Uma estratégia de alfabetização midiática em benefício do tratamento penitenciário na Espanha
Prisoners in Spain also have the right to communicate and freely express their thoughts and ideas. This condition can be a reason to implement media literacy workshops in prisons, using radio as a tool for communication and expression. Even though they are not exempt from institutional control, as they are integrated into the so-called Individualized Penitentiary Treatment Plan, prisoners enhance their social and personal dimensions through these radio experiences, which function as a tool for rehabilitation and recovery. The article uses a qualitative methodology to analyze letters written by prisoners published in a book and interviews with 26 other inmates, all participants in Spanish prison radio programs, to understand their perception of the advantages of carrying out this activity. Through discourse analysis, it is possible to observe how they recognize improvements in their communication skills, self-perception of their abilities, enhanced self-esteem, improved relationships with others, and motivation to learn. The article concludes that these workshops help achieve the empowering objective of penitentiary treatment, although they still need a communication-oriented perspective
Keywords: prisiones; presos; radio; alfabetización mediática; España; prisons; prisioners; radio; Spain; media literacy; Scopus